Bryan Stanley Turner's Philosophical Thoughts: Citizenship Outline Analysis - Ahmad Dumaeri; Samsuri samsuri (Journal of Social Research, 2024)
Bryan Stanley Turner is a professor of sociology and politics who was born in Birmingham, England on January 14, 1945. Bryan S Turner is also a director of the religious committee at The City University Of New York. He is also the director of the Centre for Contemporary Islamic Studies at the University of Western Sydney. Not stopping there, Brayen is also registered as a member of the American Sociological Research Association. This study uses a literature study. Literature study research is oriented to theories relevant to research problems. In this satisfaction study, it analyzes Bryan Stanley Turner's journal of philosophical thought about the analysis of the outline of citizenship published in 1990 in the British Sociological Association and several other relevant reading sources. Turner's view of the conception of citizenship is a set of rights and obligations that give a formal legal identity to individuals. These legal and formal rights have historically been united as a set of social institutions such as the jury system, parliaments and the welfare state. Bryan Turner offered a revised model of citizenship that included legal rights (or civil rights in the Marshall model), political rights, social rights and human rights.